Shaping Polarization Of Tumor-Associated Macrophages In Cancer Immunotherapy - Gao, Jing; Liang, Yuanzheng; Wang, Liang (Frontiers in Immunology, 2022)
Different stimuli can polarize macrophages into two basic types, M1 and M2. Tumor-associated macrophages (TAMs) in the tumor microenvironment (TME) are composed of heterogeneous subpopulations, which include the M1 anti-tumor and M2 pro-tumor phenotypes. TAMs predominantly play a M2-like tumor-promoting role in the TME and regulate various malignant effects, such as angiogenesis, immune suppression, and tumor metastasis; hence, TAMs have emerged as a hot topic of research in cancer therapy. This review focuses on three main aspects of TAMs. First, we summarize macrophage polarization along with the effects on the TME. Second, recent advances and challenges in cancer treatment and the role of M2-like TAMs in immune checkpoint blockade and CAR-T cell therapy are emphasized. Finally, factors, such as signaling pathways, associated with TAM polarization and potential strategies for targeting TAM repolarization to the M1 pro-inflammatory phenotype for cancer therapy are discussed.